Treadmills. Kinematic variability, uses in therapy and effects on muscle activity (Nova Science Publishers, 2013)
In this book, the authors present current research in the study of the kinematic variability, uses in therapy and effects on muscle activity of treadmills. Topics discussed include a treadmill's effect on motor control and variability in human gait pattern; temporo-spatial and kinematic variables in the context of rehabilitation following treadmill walking; evaluation of gait stability based on recovery steps in perturbed gait; and the effects of treadmill walking on muscle activity and neuromuscular junction of botulinum toxin-induced muscle atrophy. (Imprint: Novinka)